Kritik Ideologi Kenabian Mirza Gulam Ahmad - Fadlan Kamali Batubara (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2017)
Since its appearance in the 19th century, Ahmadiyah movement has spread throughout the world. At the center of its emergence, the movement gained support from both Muslims and Hindu conversions. While in other parts of the world, Ahmadiyah was brought by Ahmadi migrants and preachers (muballig) which deliberately sent from Lahore. The emergence of this movement is an excess of British imperialism to India accompanied by the spreading of the Christian religion and the weakening of the religious morality of Muslims. Mirza Gulam Ahmad was born and claimed to be a Messiah for the fall of Muslims in India at that time. This confession is followed by the conviction that his presence is a God’s will to save Muslims. This is the foundation of Ahmadiyah theology that developed throughout the world. The foundations of theology gained reactions from other Muslim groups including in Indonesia. For Muslims, the admission of a prophet after the prophet Muhammad is a heresy. Therefore, Mirza Gulam Ahmad and and his movement Ahmadiyah is a form of apostasy from the foundations of Islamic theology. This article will explain how the Ahmadiyah movement was formed, its theological foundations and the criticism of Ahlu al-Sunnah wa al-Jamaah against Ahmadiyah teology. Using the primary sources of Ahmadiyah and references from the salafist scholars this article discusses both views on theology especially regarding prophecy and revelation. I concluded that the Ahmadiyah movement is a deviant movement of Islam and its theological beliefs are totally incompatible with the theological foundations of Islam.